Mortality in neonates with giant omphalocele subjected to a surgical technique in Barranquilla, Colombia from 1994 to 2019 (2011)
ABSTRACT : No studies of the efcacy and safety of surgical techniques for the primary closure of giant omphalocele have been performed in Colombia. To determine the mortality rate and factors associated with mortality in neonates with giant omphalocele subjected to the surgical technique of early closure with a surgical silo described by Abello in Barranquilla, Colombia from 1994 to 2019. Retrospective cohort study of 30 neonates diagnosed with giant omphalocele and subjected to early closure of the defect. Medical history data were collected, information bias was controlled for, and descriptive statistical analysis was performed using Fisher’s exact test and the Mann–Whitney U test in SPSS 25.0. Of the patients in the cohort, 36.7% presented technique-related complications, 56.7% developed sepsis, 23.3% had low birth weight, 26.7% were preterm births, 43.3% had other malformations, 26.7% had congenital heart defects, and 13.3% presented pulmonary hypertension. The mean hospital stay was 26 days. The mortality rate was 16.7%; it was signifcantly higher among patients with other malformations, congenital heart defects, pentalogy of Cantrell and pulmonary hypertension. The Abello technique for the treatment of giant omphalocele showed a high neonatal survival rate and a low rate of procedure-related complications. The main factors associated with the death of neonatal patients were the presence of other malformations, congenital heart defect, pentalogy of Cantrell and pulmonary hypertension.